Evaluation of Some Oxidative Stress Parameters in Iraqi Patients with Inflammatory Bowel Disease - Hisham A. Shaker (Journal of Global Pharma Technology, 2016)
Objectives: Inflammatory bowel disease (IBD) refers to chronic inflammations that affect any part of the gastrointestinal tract (GIT). This study aimed to evaluate of some oxidative stress parameters (TOC, TAC, OSI and MDA) in sera of Iraqi patients with IBD. Methods: Three main groups were included in this study; 30 patients (15male &15female) with Crohn’s disease (CD group), 30 patients (15male & 15female) with ulcerative colitis (UC group) and 30 (15female & 15female) apparently healthy controls (HC group) comparable for age and gender without a history of IBD were involved in the current study. Results: TOC in the sera of both patient groups (CD&UC) was a highly significant increase (p<0.001) when compared to the (HC group) while significant decrease (p<0.05) in the TAC of (CD group), as well as highly significant decrease (p<0.001) in the TAC of (UC group) was observed in comparison with their levels in corresponding (HC group). A highly significant increase (p<0.001) in serum (OSI) of two patient groups (CD & UC) in comparison to that of (HC group).Meanwhile, significant increase (p<0.05) in serum MDA concentration of both patient groups (CD & UC) when compared to that of the (HC group) was observed. Conclusion: We found a significant increase in TOC, OSI and MDA while a significant decrease in TAC of patient groups. Therefore, CD and UC subjected to an increased in oxidative stress situation.Keywords: Inflammatory bowel disease, Crohn’s disease, Ulcerative colitis, Oxidative stress.